1988
DOI: 10.1093/carcin/9.5.797
|View full text |Cite
|
Sign up to set email alerts
|

UVR induction of TGFα: a possible autocrine mechanism for the epidermal melanocytic response and for promotion of epidermal carcinogenesis

Abstract: The occurrence of the epidermal growth factor homologue, transforming growth factor alpha (TGF alpha), in embryonic and neoplastic tissues suggests that it may be an oncofetal version of epidermal growth factor. A strong case is developing for TGF alpha to have an autocrine mode of action in sustaining the autonomous growth of several types of tumour. We propose that TGF alpha normally has an autocrine role not only in stimulating the growth of some fetal tissues but also with postnatal epidermal cells in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 0 publications
2
36
0
Order By: Relevance
“…Cells-To identify the molecule that mediates the UVB-induced activations of EGFR and MAPKs, conditioned medium from UVB-irradiated HaCaT cells was examined to determine whether it could activate EGFR and MAPKs of nonirradiated cells, because UV irradiation is known to release various growth factors and cytokines that can activate EGFR (16,27). Treatment of nonirradiated HaCaT cells with the conditioned medium obtained from UVB-irradiated HaCaT cells induced the phosphorylations of EGFR, p38, and ERK but not that of JNK, in contrast to UVB, which induced the phosphorylations of all three MAPKs, including JNK (Fig.…”
Section: G␤␥ Augmented the Activity That Phosphorylates Egfr P38 Anmentioning
confidence: 99%
“…Cells-To identify the molecule that mediates the UVB-induced activations of EGFR and MAPKs, conditioned medium from UVB-irradiated HaCaT cells was examined to determine whether it could activate EGFR and MAPKs of nonirradiated cells, because UV irradiation is known to release various growth factors and cytokines that can activate EGFR (16,27). Treatment of nonirradiated HaCaT cells with the conditioned medium obtained from UVB-irradiated HaCaT cells induced the phosphorylations of EGFR, p38, and ERK but not that of JNK, in contrast to UVB, which induced the phosphorylations of all three MAPKs, including JNK (Fig.…”
Section: G␤␥ Augmented the Activity That Phosphorylates Egfr P38 Anmentioning
confidence: 99%
“…There are several reports of the production of TGF-oa by melanoma cell lines (Marquardt et al, 1983;Derynck et al, 1987;Ellem et al, 1988). Since TGF-a has been considered to be one of the possible autocrine growth factors in cancer cells, several studies were performed previously to clarify the role of TGF-a as the autocrine growth factor for melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Singletary et al (1987) reported that EGF enhanced the growth of almost all melanoma cells prepared from surgical specimens. Ellem et al (1988) reported that in melanoma cells and melanocytes the secretion of TGF-a was stimulated by ultraviolet radiation and that TGF-a promoted their own growth. In contrast, Kudlow et al (1984) reported that a monoclonal antibody against EGF receptor did not inhibit the cellular growth of a melanoma cell line, suggesting that TGF-oc could not function as an autocrine growth factor for melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 UV exposure also alters receptor degradation [3][4][5][6] and increases EGFR ligand expression. 7,8 Activation of EGFR by UV stimulates both MAPK and phosphatidyl inositol 3-kinase/Akt signaling. 9 EGFR activation also suppresses apoptosis, increases proliferation, delays hyperplasia, and increases skin carcinogenesis following UV exposure.…”
mentioning
confidence: 99%